Emission of radio waves in particle showers : validation of microscopic simulations with the SLAC T-510 experiment and their potential in the future square kilometre array /: validation of microscopic simulations with the SLAC T-510 experiment and their potential in the future square kilometre array. (2017) - Unknown
No abstract available